PAIN RELIEF WITH PREVENTIVE MEASURES AMONG KNEE OSTEOARTHRITIS PATIENTS: A COMPARISON BETWEEN FOLLOWERS VERSUS NON FOLLOWERS - Muhammad Ikram (Army Medical College Rawalpindi, 2020)
Objective: To compare mean pain scores among knee osteoarthritis patients following or not following preventive measures.